The Relationship of Risk Factors to Incidence Prediabetes Young Age Groups - Heri Nugroho Hario Seno; Ardhia Amelia Savitri; Edward Kurnia Setiawan; Meita Hendrianingtyas (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Prediabetes is increasingly prevalent among young adults, presenting a critical opportunity for early intervention to prevent the onset of type 2 diabetes and associated cardiovascular complications. This study investigates the association between selected lifestyle-related risk factors and prediabetes incidence among undergraduate medical students. A total of 50 students from Diponegoro University (cohorts 2021 and 2022) were enrolled through purposive and random sampling methods. Clinical assessments included fasting blood glucose and 2-hour oral glucose tolerance tests, analyzed using the hexokinase method. Data on obesity (body mass index), sleep quality (Pittsburgh Sleep Quality Index), physical activity (International Physical Activity Questionnaire-Short Form), and family history of diabetes were collected through validated instruments. The prevalence of prediabetes was significantly higher among students with obesity (p < 0.001), poor sleep quality (p = 0.048), low physical activity (p = 0.005), and a family history of diabetes (p = 0.006). Multivariate analysis identified obesity as the most influential independent predictor (OR 7.30, 95% CI: 1.61-33.20, p = 0.010). These findings highlight the urgent need for preventive strategies targeting modifiable risk factors in young populations. Interventions focusing on healthy weight management, regular physical activity, and sleep hygiene may play a pivotal role in mitigating early metabolic risk Keywords: Prediabetes, Young Adults, Sleep Quality, Physical Activity, Medical Students